The effects from the usage of construction materials towards the environmental degradation / Nurelisma Sharina Rozmi and Natasha Khalil - Rozmi, Nurelisma Sharina; Khalil, Natasha (2023)
The selection and application of construction materials has a significant impact on the outcome and sustainability of construction projects. It contributes towards the effects of construction materials on a variety of aspects like environmental sustainability and human health. The selection of suitable materials is critical in determining the project's environmental footprint, as traditional materials frequently contribute to high carbon emissions. Therefore, this research aims to identify the effects from the usage of the construction materials towards the environmental degradation and to suggest the best strategies to overcome the problems. The data were collected from the respondent through online questionnaire survey. A total of 137 questionnaire disturbributed to the Architects and Engineers in Pulau Pinang that works at registered firms with Board of Architects Malaysia (LAM) and Board of Engineers (BEM) and received 45 responses. The findings revealed that the construction materials have a big impact on the environment and some strategies in selection of construction materials has been suggested and it is hoped that the findings contributed to the awareness and implementation of more sustainable and eco-friendly practices in the construction industry.